Aplikasi Website Pada Toko Buket Bunga Fhaflorist Kroya Dengan Metode Waterfall - Alifah, Putri Eka Nur; Prasetyo, Muhamad Awiet Wiedanto; Affrad, Mahazam (Journal of Advanced Research in Informatics, 2025)
In the Industry 4.0 to 5.0 era, small and medium enterprises (SMEs) increasingly adopt technology to improve operational efficiency. FhaFlorist Kroya Flower Shop still records transactions and manages products manually, resulting in data-entry errors and slow reporting. This study designs and implements a web-based cashier application using Laravel (PHP) according to the Waterfall model comprising requirements analysis, system design, implementation, testing, and maintenance each phase completed on schedule and to specification. Functional testing was carried out via Black-box Testing, followed by a User Acceptance Test (UAT) to verify end-user acceptance. The UAT yielded a system viability score of 91.20%, indicating that the application meets user requirements and is suitable for enhancing the shop’s operational processes